2021
DOI: 10.3390/app112210709
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Three Different Digital Cement Spacers on the Marginal Gap Adaptation of Zirconia-Reinforced Lithium Silicate Crowns Fabricated by CAD-CAM System

Abstract: Background: This study compared the influence of three different radial spacers (60,90,120 microns) on the marginal gap adaptation by using computer-aided manufacturing (CAD-CAM) for producing monolithic zirconia reinforced lithium silicate (ZLS) ceramic crowns. Methods: A total of 45 abutment acrylic teeth were divided into three groups of different radial spacers (60, 90, and 120 microns). In each group 15 teeth were scanned by Omnicam intra oral scanner and ZLS crowns were ground. For each unit the marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In this research we used a previous method which we already used before and was published in our previous research [12]. Forty-ve machine-made identical plastic teeth (FLUX 8634; Columbia Dentoform, upper right rst molars) were used, Occlusal clearance 2mm, axial convergence angle of 6 degree and shoulder nish line at the width of 1.2mm all around.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research we used a previous method which we already used before and was published in our previous research [12]. Forty-ve machine-made identical plastic teeth (FLUX 8634; Columbia Dentoform, upper right rst molars) were used, Occlusal clearance 2mm, axial convergence angle of 6 degree and shoulder nish line at the width of 1.2mm all around.…”
Section: Methodsmentioning
confidence: 99%
“…,9 years of experience) marked the nish and a virtual single x partial denture design (CEREC SW 5.2.4; Dentsply Sirona) was created with the following digital parameters: radial spacer: 90 µm, occlusal spacer 120 µm, proximal contacts strength:25 µm, occlusal contacts strength:25 µm, radial minimal thickness:1000 µm, occlusal minimal thickness:1500 µm, margin thickness:100 µm, margin ramp width:100 µm, margin ramp angle:60º. It is important to mention that due to the results of our previous research [12] we used a 90 µm radial spacer for all ZLS crowns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twist Hackles 77 ns on the CAD software. 23 The current study employed airborne particle abrasion with alumina particles (sandblasting) to raise the zirconia crown's surface energy, wettability, and roughness.…”
Section: Cement Layermentioning
confidence: 99%
“…It has been shown that crowns with reduced cement spacers lead to an increased marginal discrepancy due to a reduction in the passive fit on the abutment. A study that evaluated the marginal gap adaption of CELTRA ® DUO (CELTRA ® DUO, Sirona Dentsply, Milford, DE, USA) with different digital radial spacers set at 60, 90, and 120 µm and measured the marginal gap in four regions by scanning electron microscope (SEM) concluded that the preferable radial spacer for CELTRA ® DUO (CELTRA ® DUO, Sirona Dentsply, Milford, DE, USA) crowns is 90 µm [ 12 ].…”
Section: Introductionmentioning
confidence: 99%